Calreticulin promotes angiogenesis via activating nitric oxide signalling pathway in rheumatoid arthritis. (November 2014) - Ding, H.; Hong, C.; Wang, Y.; Liu, J.; Zhang, N.; Shen, C.; Wei, W.; Zheng, F.
Summary Calreticulin (CRT) is a multi‐functional endoplasmic reticulum protein implicated in the pathogenesis of rheumatoid arthritis (RA). The present study was undertaken to determine whether CRT was involved in angiogenesis via the activating nitric oxide (NO) signalling pathway. We explored the profile of CRT expression in RA (including serum, synovial fluid and synovial tissue). In order to investigate the role of CRT on angiogenesis, human umbilical vein endothelial cells (HUVECs) were isolated and cultured in this study for in‐vitro experiments. Our results showed a significantly higher concentration of CRT in serum (5·4 ± 2·2 ng/ml) of RA patients compared to that of osteoarthritis (OA, 3·6 ± 0·9 ng/ml, P < 0·05) and healthy controls (HC, 3·7 ± 0·6 ng/ml, P < 0·05); and significantly higher CRT in synovial fluid (5·8 ± 1·2 ng/ml) of RA versus OA (3·7 ± 0·3 ng/ml, P < 0·05). High levels of CRT are expressed in synovial membrane localized predominantly to inflammatory cells and synovial perivascular areas in both the lining and sublining layers of RA synovial tissue (RAST). Increased nitric oxide (NO) production and phosphorylation level of endothelial nitric oxide synthase (eNOS) were measured in HUVECs following CRT stimulation, while the total eNOS expression was not significantly changed. Furthermore, CRT promoted the proliferation, migration and tube formation of HUVECs, which were significantly inhibited by a specific eNOS inhibitor. These findings suggested that CRT may be involved in angiogenesis events in RA through NO signalling pathways, which may provide a potential therapeutic target in the treatment of RA.